AB0581 HIGH PREVALENCE OF TUBERCULOSIS IN ADULTS AND CHILDREN WITH IIM AS COMPARED WITH SLE: RETROSPECTIVE DATA REVIEW FROM A LARGE COHORT AT A TERTIARY CARE CENTER IN INDIA. (2nd June 2020) - Gupta, L.; Zanwar, A.; Aggarwal, R.; Lawrence, A.; Misra, D.; Agarwal, V.; Misra, R.; Aggarwal, A.
Abstract : Background: Infections are the most common cause of morbidity and mortality in idiopathic inflammatory myositis (IIM). India is endemic for Tuberculosis (TB) with a prevalence of 2.3 cases per thousand population. Objectives: Thus, we studied the prevalence of TB in our cohort of IIM patients and compared with that in systemic lupus erythematosus (SLE). Methods: Medical records from paper charts and electronic medical records were reviewed for adults and juvenile patients with SLE (ACR criteria 1997) and IIM (Bohan and Peter criteria 1975) first presented at a tertiary care hospital in India from 1989 to 2016. Clinical variables including disease characteristics variables, the frequency, site, duration and complication of active TB as well as dose of corticosteroids and other immunosuppressive drugs were extracted retrospectively from the medical records. Descriptive statistics were used to describe the cohort and TB characteristics. Chi-square and t-test were used to evaluate association of TB with clinical diagnosis as well as medication data. Results: There were 167 (132 adults and 35 juvenile) IIM and 280 (131 adults and 149 juvenile) SLE in our cohort. Active TB occurred in 24 (14.4%) of all IIM cases (18, 13.6% adults; 6, 17.1% juvenile) as compared to 18 (6.4%) of all SLE cases (8, 6.1% adults; 10, 6.7% juvenile, p value < 0.01). Of all the TB in myositis, most often it was seen in Dermatomyositis (n=11, 45.8%) followed by Polymyositis (5, 20.8%), and occasionally in Overlap myositis (3, 12.5) and juvenile dermatomyositis (1, 4.1%). Considering an annual TB rate of 211 per 100, 000 of the general population, the risk of developing active TB was 62-fold higher in patients with IIM and 27-fold higher in those with lupus. Patients with IIM had higher odds of developing TB as compared with Lupus [odds ratio 2.86 (CI 1.5-5.47), p=0.007). Amongst 24 IIM patients with TB, 10 had pulmonary TB and 14 had extra-pulmonary TB. The median glucocorticoid dose at the diagnosis of TB was 0.25 (0-1.5) mg/kg/day. Half the cases of active TB occurred during inactive myositis. Seventeen patients with active TB were followed up over 27 months (8-184), with remission of TB in all cases but required prolonged courses of Anti-Tuberculous Therapy (ATT) in 25% cases with 10 ATT related adverse events in 8 patients and 5 patients with relapse of myositis due to lowering of immunosuppression. Conclusion: Patients with IIM have higher prevalence of active TB as compared with SLE patients. The risk is highest in patients with Dermatomyositis possibly related to high doses of steroids. Extra-pulmonary forms of TB are more common, and patients commonly require prolonged course of ATT and may suffer relapses of myositis during ATT. Screening for latent TB may be useful in IIM patients before prescribing steroids and other immunosuppressive drugs. References: [1]TB Statistics India | National, treatment outcome & state statistics [Internet]. TB Facts | TB, tests, drugs, statistics. [cited 2019 Jun 13]. Available from: https://www.tbfacts.org/tb-statistics-india/ [2]Muhammed H, Gupta L, Zanwar A, Misra DP, Lawrence A, Agarwal V, Aggarwal A, Misra R;OPC0243: Infections are leading cause of in-hospital mortality in patients with inflammatory myositis; Indian J Rheumatol 2018;13, Suppl S2:93-241 [3]Gaitonde S, Pathan E, Sule A, Mittal G, Joshi VR. Efficacy of isoniazid prophylaxis in patients with systemic lupus erythematosus receiving long term steroid treatment. Ann Rheum Dis. 2002 Mar;61(3):251–3. [18]He D, Bai F, Zhang S, Jiang T, Shen J, Zhu Q, et al. High incidence of tuberculosis infection in rheumatic diseases and impact for chemoprophylactic prevention of tuberculosis activation during biologics therapy. Clin Vaccine Immunol CVI. 2013 Jun;20(6):842–7. Disclosure of Interests: Latika Gupta: None declared, Abhishek Zanwar: None declared, Rohit Aggarwal Grant/research support from: Pfizer, Genentech, BMS, Mallinckrodt, Consultant of: Pfizer, Genentech, BMS, Mallinckrodt, Bristol Myers-Squibb, octapharma, CSL Behring, AstraZeneca, Corbus, Kezar, Abbvie, Able Lawrence: None declared, Durga Misra: None declared, Vikas Agarwal: None declared, Ramnath Misra: None declared, Amita Aggarwal: None declared